2018
DOI: 10.1159/000492756
|View full text |Cite
|
Sign up to set email alerts
|

Association of Benign Paroxysmal Positional Vertigo with Osteoporosis and Vitamin D Deficiency – A Case-Control Study

Abstract: Background: Benign paroxysmal positional vertigo (BPPV) is a common type of vertigo involving the peripheral vestibular system. Consensus on the factors causing BPPV is limited. Due to the uncertainty of etiological factors causing BPPV, most cases are accepted as idiopathic. Calcium metabolism plays a primary role in the synthesis and absorption of otoconia primarily made of calcium carbonate and, thus, might be an etiological factor in the onset of BPPV. Objective: To study the role of osteoporosis and vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…There was a preponderance of female patients among the cases, with 33(67.3%) female patients, and 16 (32.7%) male patients. This was in line with a previous study, 11 which reported that BPPV is common among females.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…There was a preponderance of female patients among the cases, with 33(67.3%) female patients, and 16 (32.7%) male patients. This was in line with a previous study, 11 which reported that BPPV is common among females.…”
Section: Discussionsupporting
confidence: 93%
“…The mean age of the patients in our study was 44.39 years. This observation is in line with past researches, 11,12 which indicated that BPPV is not a common disease among the younger age group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A statistically significant difference was observed in the mean serum vitamin D3 levels and the deficiency prevalence between the two groups. 18 Ca 2+ and carbonate ions are of crucial importance for vertebrate otoconia production. Besides, Ca 2+ is required to mineralize otoconia and to maintain any turnover in the otolith, because the otoconia has a dynamic state.…”
Section: Discussionmentioning
confidence: 99%